Can preoperative myocardial perfusion scintigraphy predict changes in left ventricular perfusion and function after coronary artery bypass graft surgery? - Eckardt, Rozy (Oxford University Press, 2012)
OBJECTIVES: We wanted to evaluate whether preoperative myocardial perfusion scintigraphy (MPS) could predict changes in cardiac symptoms and postoperative myocardial perfusion and left ventricular function after coronary artery bypass grafting (CABG). METHODS: Ninety-two patients with stable angina pectoris (and at least one occluded coronary artery) underwent MPS before, and 6 months after, undergoing CABG. The result of the MPS was kept secret from the surgeons. RESULTS: Before CABG, 90% of the patients had angina. After CABG, 97% of the patients were without symptoms. Overall graft patency was 84%. Before CABG, one patient had normal perfusion; in the rest of them the defects were classified as follows: reversible (60%), partly reversible (27%) and irreversible (12%). Following CABG, 33% had normal perfusion; in the rest the defects were reversible in 29%, partly reversible in 12% and irreversible in 26%. Left ventricular ejection fraction (LVEF), which was normal before operation in 45%, improved in 40% of all patients. The increase in LVEF was not related to the preoperative pattern of perfusion defects. Of 30 patients with normalized perfusion after CABG, 29 (97%) had reversible defects and one patient had partly reversible defects. Of 83 perfusion defects, which were normalized after CABG, 67 were reversible (81%) or partly reversible (12%). Seventy-five percent of all reversible coronary artery territories before CABG were normalized after operation. CONCLUSIONS: Our results indicate that reversible or partly reversible perfusion defects at a preoperative MPS have a high chance of normalized myocardial perfusion assessed by MPS 6 months after operation. Normal perfusion is obtained almost exclusively in territories with reversible ischaemia. Symptoms improved in nearly all patients and LVEF in a significant fraction of the patients, not related to preoperative MPS.